Seasonal Variations in Cataract Surgery Numbers in Mid Western and Far Western Terrain Belts of Nepal - Bastola, Pradeep; Bascaran, C.; Foster, A. (Journal of Nepalgunj Medical College, 2016)
Introduction: In western regions of Nepal many more cataract operations are performed during the winter season than the summer season. This causes problems with resource allocation. The aim of this study was to assess the magnitude of seasonal variation in cataract surgery, explore the causes, and make recommendations to optimize resource utilization. Methods: Hospital data of the number of patients undergoing cataract surgery in the years 2011, 2012 and 2013 in 3 hospitals was analyzed by month of surgery. 100 consecutive patients having cataract surgery in the winter season and 100 in the summer season were compared for differences and questioned as to the reasons for choosing cataract surgery at that time. Results: Of the 127,718 cataract operations performed over 3 years in the 3 hospitals, 45% were performed in the 3 months February-April and 9% in the 3 months June-August. The mean number performed in March (highest volume month) was more than 7 times higher than that performed in July (lowest month) – 8016 versus 1041 per month. At univariate level nationality, marital status, socioeconomic status, cost per surgery, occupation, age and ethnicity were associated with seasonal variations. Multivariate logistic regression analysis of seasonal uptake showed Nationality/Ethnicity, Socioeconomic status and cost per surgery statistically significant in predicting attendance in high season. Conclusions: There is a large seasonal variation in cataract surgery numbers in West Nepal. Factors including patients' nationality cost of surgery and cultural beliefs contribute to the seasonal variation. If these can be addressed then resource allocation and utilization can be improved. JNGMC Vol. 12 No. 2 December 2014, Page: 24-29